Synthesis of Code Anomalies: Revealing Design Problems in the Source Code - Oizumi, Willian N.; Garcia, Alessandro F. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2016: Anais do XXIX Concurso de Teses e Dissertações, 2016)
Design problems affect most software projects and make their maintenance expensive and impeditive. Thus, the identification of potential design problems in the source code – which is very often the only available and upto-date artifact in a project – becomes essential in long-living software systems. This identification task is challenging as the reification of design problems in the source code tend to be scattered through several code elements. However, stateof-the-art techniques do not provide enough information to effectively help developers in this task. In this work, we address this challenge by proposing a new technique to support developers in revealing design problems. This technique synthesizes information about potential design problems, which are materialized in the implementation under the form of syntactic and semantic anomaly agglomerations. Our evaluation shows that the proposed synthesis technique helps to reveal more than 1200 design problems across 7 industry-strength systems, with a median precision of 71% and a median recall of 78%. The relevance of our work has been widely recognized by the software engineering community through 2 awards and 7 publications in international and national venues.